The Optimization Strategy of Restaurant Tax Collection in The Government of Sleman District, 2013 - 2015 - Nuryanto (ARTOKULO : Journal of Accounting, Economic and Management, 2024)
The purpose of this paper is to present the results of an in-depth analysis of the strategic factors that have influence the development of restaurant taxes in Sleman Regency Government, namely a summary of the internal strategic factor analysis (IFAS) and a summary of the External Strategic Factor Analysis (EFAS) from this research. This paper aims to provide an overview of IFAS and EFAS, focusing on the key factors that affect the development and implementation of the strategy, and to provide a reference for the strategic planning of the restaurant tax. The research method used in this research is descriptive qualitative. Data was obtained through interviews, questionnaires and documentation studies. The research data was processed, then a SWOT analysis was carried out. By identifying opportunities, threats, strengths and weaknesses with analysis of external and internal factors, the right strategy has been produced for the Sleman Regency Government, namely the strategy of using strengths to take advantage of opportunities (Strength Opportunity).